The crisis counseling and traumatic events treatment planner - Kolski, Tammi D. (Practice planners ;, 2012)
"Individuals in crisis need specialized interventions that are unlike other forms of therapy. The Crisis Counseling and Traumatic Events Treatment Planner, Second Edition provides a framework to offer crisis intervention effectively while incorporating the criteria necessary for managed care review and insurance reimbursement. The new edition has been thoroughly updated and provides all the elements necessary to quickly and easily develop formal treatment plans that satisfy the demands of HMOs, managed care companies, third-party payors, and state and federal agencies"--